2010
DOI: 10.1038/nrm2928
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear pore complex: bridging nuclear transport and gene regulation

Abstract: Although the nuclear pore complex (NPC) is best known for its primary function as the key regulator of molecular traffic between the cytoplasm and the nucleus, a growing body of experimental evidence suggests that this structure participates in a considerably broader range of cellular activities on both sides of the nuclear envelope. Indeed, the NPC is emerging as an important regulator of gene expression through its influence on the internal architectural organization of the nucleus and its apparently extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
466
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(473 citation statements)
references
References 173 publications
6
466
0
1
Order By: Relevance
“…38,39 In the opisthokonts and plants, the nuclear basket is composed of large (»200-250 kDa) coiled coil proteins, that associate with and coordinate several nuclear peripheral processes, thereby extending NPC functionality. 36,62,[75][76][77][78] Although the 2 nuclear basket proteins are much smaller (»100kDa) in trypanosomes, our study showed by iEM, that they extend an average of 36nm into the nucleoplasm from the center of the TbNPC. 5 Additionally, they have retained similar functions to those in other eukarya, by creating heterochromatin free zones around nuclear pores that are evident by electron microscopy in all eukaryotic nuclei, as well as recapitulating interactions with the spindle organizer.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 In the opisthokonts and plants, the nuclear basket is composed of large (»200-250 kDa) coiled coil proteins, that associate with and coordinate several nuclear peripheral processes, thereby extending NPC functionality. 36,62,[75][76][77][78] Although the 2 nuclear basket proteins are much smaller (»100kDa) in trypanosomes, our study showed by iEM, that they extend an average of 36nm into the nucleoplasm from the center of the TbNPC. 5 Additionally, they have retained similar functions to those in other eukarya, by creating heterochromatin free zones around nuclear pores that are evident by electron microscopy in all eukaryotic nuclei, as well as recapitulating interactions with the spindle organizer.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…Thus, quality control occurs at the nuclear basket and nucleoplasmic FGNups and then the remodeling of mRNPs to facilitate export occurring at the cytoplasmic end of the NPC. 15,62 In any case, all this underscores the intimate link between the NPC and gene expression, as well as the incredible flexibility of the NPC, which although probably fully formed at LECA has the capacity to mold and adapt its structure to the demands of individual lineages by acting as an interaction platform for several nuclear processes while still maintaining its structural core and primary function as a transport hub.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…For instance, NPC destabilization may result from the association of Nups and integrated proviral cDNA or nuclear vRNA during transcription (Capelson et al, 2010;Hou and Corces, 2010;Strambio-De-Castillia et al, 2010). HIV-1 may disrupt NPCs to evade antiviral responses, as seen in other viruses (Gustin and Sarnow, 2002;Fontoura et al, 2005;Bardina et al, 2009;Porter and Palmenberg, 2009;Atasheva et al, 2010;Ren et al, 2010).…”
Section: Nup62 Is Essential For Hiv-1 Vrna Exportmentioning
confidence: 99%
“…A heat map of spatial locations of translocating clusters indicated a hotspot of comparable volume to the nuclear pore complexes and accessory structures [65,66] (Figure 1(e)). The dwell time during nuclear envelope translocation was ~10 ms, similar to previous estimates for transport factors [67] but here found to be insensitive to glucose (Figure 1(f)), demonstrating that there is no direct selectivity on the basis of TF phosphorylation state by nuclear pore complexes themselves which suggests that cargo selectivity mechanisms of nuclear transport [68] are blind to phosphorylation state.…”
Section: Resultsmentioning
confidence: 99%